Vitexin Possesses Anticonvulsant and Anxiolytic-Like Effects in Murine Animal Models - de Oliveira, Denise Dias; da Silva, Cassio Prinholato; Iglesias, Bruno Benincasa; Beleboni, Renê O. (Frontiers in Pharmacology, 2020)
Different types of epilepsy and forms of pathological anxiety have been described as significant neurological disorders that may exist as comorbidities. Some of those disorders share the association of affected limbic areas/neuropathological triggers as well as the use of drugs for their clinical management. The aim of this work was to investigate the anticonvulsant and anxiolytic properties of the vitexin (apigenin-8-C-glucoside), since this compound is a flavonoid usually found as one of the major constituents in several medicinal plants claimed as anxiolytics and/or anticonvulsants. This investigation was performed by the use of a series of classical murine animal models of chemically induced-seizures and of anxiety-related tests (open-field, elevated plus-maze and light-dark box tests). Here, we show that the systemic administration of vitexin (1.25; 2.5 and 5 mg/kg; i.p) exhibited selective protection against chemically-induced seizures. Vitexin did not block seizures evoked by glutamate receptors agonists (NMDA and kainic acid) and it did not interfere with the latencies for these seizures. Conversely, the same treatments protected the animals in a dose-dependent manner against the seizures evoked by the Gabaergic antagonists picrotoxin and PTZ and rise the latency time for the first seizure on non-protected animals. The higher dose of vitexin protected 100% of animals against the tonic-clonic seizures triggered by GABA antagonists. The results from open-field, elevated plus-maze and light-dark box tests indicated the anxiolytic properties of vitexin at similar range of doses described for the anticonvulsant action screening. Furthermore, these results pointed that vitexin did not cause sedation or locomotor impairment on animals. The selective action of vitexin against picrotoxin and PTZ may reinforce the hypothesis by which this compound acts mainly by the modulation of GABAergic neurotransmission and/or related pathways. This could be useful to explain the dual activity of vitexin as anticonvulsant and anxiolytic, and highlight the pharmacological interest on this promising flavonoid.